2011
DOI: 10.1007/s12274-011-0112-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbial reduction of graphene oxide by Shewanella

Abstract: Graphene oxide (GO) can be reduced to graphene in a normal aerobic setup under ambient conditions as mediated by microbial respiration of Shewanella cells. The microbially-reduced graphene (MRG) exhibited excellent electrochemical properties. Extracellular electron transfer pathways at the cell/GO interface were systematically investigated, suggesting both direct electron transfer and electron mediators are involved in the GO reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
213
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(230 citation statements)
references
References 34 publications
(47 reference statements)
13
213
0
4
Order By: Relevance
“…147 In another example, Wang et al demonstrated the reduction of graphene oxide mediated by microbial respiration of Shewanella cells in a normal aerobic setup under ambient conditions. 148 Shewanella, the metal-reducing bacterium is known to transfer metabolically-generated electrons from the interior part of the cell to external electron acceptors such as solid metal oxides. For the reduction of graphene oxide, extracellular electron transfer is mediated by both, self-secreted electrons and outer membrane c-type cytochromes (Mtr/Ornc).…”
Section: Figmentioning
confidence: 99%
“…147 In another example, Wang et al demonstrated the reduction of graphene oxide mediated by microbial respiration of Shewanella cells in a normal aerobic setup under ambient conditions. 148 Shewanella, the metal-reducing bacterium is known to transfer metabolically-generated electrons from the interior part of the cell to external electron acceptors such as solid metal oxides. For the reduction of graphene oxide, extracellular electron transfer is mediated by both, self-secreted electrons and outer membrane c-type cytochromes (Mtr/Ornc).…”
Section: Figmentioning
confidence: 99%
“…(Lim et al, 2012;Bykkam et al, 2013); plant pathogen e.g., Xanthomonas oryzae and against fungi e.g., C. albicans and C. tropical (Li et al, 2013). Also several studies demonstrated and developed an environment friendly, cost effective, simple method and green approaches for the reduction of GO using microbial cells such as E. coli, Shewanella and Yeast (Gurunathan et al, 2013;Wang et al, 2011;Khanra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown the use of graphene in microbial fuel cells, 249 graphene as a scaffold for bacterial growth, 228 as well as the use of bacteria as a graphene oxide reducing agent. 250,251 Various in vitro toxicity studies have been conducted to determine the toxicity of graphene towards cancer [234][235][236][237][238] and human cell lines. 229,239 The cytotoxicity towards the cancer cell lines A549 was shown to depend largely on the cell culture medium components.…”
Section: Environmental and Biological Toxicity Of Graphenementioning
confidence: 99%